Preventive maintenance data logger monitoring system - Gunalan, Sanasie; Zul Izwan, Abdul Radzak; Muhammad Aizzat, Zakaria (Penerbit UMP, 2021)
This research presents the Preventive Maintenance Data Logger (PMDL) Monitoring System and the process of how it has been manufactured. Preventive Maintenance Data Logger Monitoring System is a device which will collect the data from vehicle’s sensor for prevention maintenance and then save the data to other storage for future analysis. Preventive Maintenance Data Logger Monitoring System also can send notification to user for crash prevention. This project comprises of mechanical system, electronic system, and software system. The methodology of the Preventive Maintenance Data Logger system and prototype development is discussed in this paper on the manufacturing processes. The software is programmed using C language in Arduino software and the notification for preventive are develop using BLYNK application. Manufacturing processes involves in making this project, including additive manufacturing, welding and cutting. Several test case studies were conducted to verify the capability of the device in term of the vehicle speed, location, crash point data, distance between other vehicles detection and reliability.